Arrival to the City - Scott Arford; Neil Cristal; Michael Dean; Christopher Mitchell; Doug Shaffer (Oz, 1991)
The projects to follow are shamanic acts, trying to heal the "eternal wound of existence," of life and architecture. The healing occurs through acts and events which constitute the discourse of arrival to an ideal city.